2015
DOI: 10.4252/wjsc.v7.i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Control of stem cell fate by engineering their micro and nanoenvironment

Abstract: Stem cells are capable of long-term self-renewal and differentiation into specialised cell types, making them an ideal candidate for a cell source for regenerative medicine. The control of stem cell fate has become a major area of interest in the field of regenerative medicine and therapeutic intervention. Conventional methods of chemically inducing stem cells into specific lineages is being challenged by the advances in biomaterial technology, with evidence highlighting that material properties are capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 116 publications
1
78
0
2
Order By: Relevance
“…They are easier to grow in cell culture and could find more diverse clinical applications, because they are pluripotent and can differentiate into cells of all three germ layers: endoderm, mesoderm and ectoderm. On the other hand, they could cause immune rejections and their proliferation and differentiation are more difficult to control [4]. Thus they could form tumors when introduced into patients unless made fully responsive to their environment.…”
Section: Mini Review Abstractmentioning
confidence: 99%
“…They are easier to grow in cell culture and could find more diverse clinical applications, because they are pluripotent and can differentiate into cells of all three germ layers: endoderm, mesoderm and ectoderm. On the other hand, they could cause immune rejections and their proliferation and differentiation are more difficult to control [4]. Thus they could form tumors when introduced into patients unless made fully responsive to their environment.…”
Section: Mini Review Abstractmentioning
confidence: 99%
“…It was shown that immobilised chemical cues are more effective than soluble factors. However, improved control over bioactivity, spacing and orientation of the immobilised growth factors is required to guide-/direct-specific stem cell differentiation [214]. Further studies investigating the effect of chemical signals on stem cell fate are summarised in …”
Section: Biochemical Signals As Stem Cell Fate Regulatorsmentioning
confidence: 99%
“…Micro-and nanopatterning techniques including soft lithography, electrospinning, layer-by-layer microfluidic patterning, three-dimensional printing, reactive ion etching and ion milling have resulted in the fabrication of scaffolds with controlled porosity, geometry and rigidity and texture [216][217][218]. The production of specific surface topography scales (nano, micro), types (ridges, pit, pillar, grooves) and distributions (random, regular) has enabled researchers to study the influence of topographical signals on stem cell differentiation [214]. Structural cues greatly affect gene expression as they determine cell shape, elongation, positioning of focal adhesion and cell-cell interactions [29,[219][220][221].…”
Section: Topographical Signals As Regulators Of Stem Cell Fatementioning
confidence: 99%
See 2 more Smart Citations